Land in balance: The scientific conceptual framework for Land Degradation Neutrality - Cowie, Annette L.; Orr, Barron J.; Castillo Sanchez, Victor M.; Chasek, Pamela; Crossman, Neville D.; Erlewein, Alexander; Louwagie, Geertrui; Maron, Martine; Metternicht, Graciela I.; Minelli, Sara; Tengberg, Anna E.; Walter, Sven; et al. (Environmental science & policy, 2018)
•Five modules provide a practical framework for implementing land degradation neutrality (LDN).•LDN aims to maintain the land-based natural capital.•LDN counterbalances expected losses with measures to achieve equivalent gains within the same land type.•The response hierarchy prioritises Avoid>Reduce>Reverse land degradation.•Indicators for monitoring are applied on a “one out, all out” basis. The health and productivity of global land resources are declining, while demand for those resources is increasing. The aim of land degradation neutrality (LDN) is to maintain or enhance land-based natural capital and its associated ecosystem services. The Scientific Conceptual Framework for Land Degradation Neutrality has been developed to provide a scientific approach to planning, implementing and monitoring LDN. The Science-Policy Interface of the United Nations Convention to Combat Desertification (UNCCD) led the development of the conceptual framework, drawing in expertise from a diverse range of disciplines. The LDN conceptual framework focuses on the supporting processes required to deliver LDN, including biophysical and socio-economic aspects, and their interactions. Neutrality implies no net loss of the land-based natural capital relative to a reference state, or baseline. Planning for neutrality involves projecting the likely cumulative impacts of land use and land management decisions, then counterbalancing anticipated losses with measures to achieve equivalent gains. Counterbalancing should occur only within individual land types, distinguished by land potential, to ensure “like for like” exchanges. Actions to achieve LDN include sustainable land management (SLM) practices that avoid or reduce degradation, coupled with efforts to reverse degradation through restoration or rehabilitation of degraded land. The response hierarchy of Avoid>Reduce>Reverse land degradation articulates the priorities in planning LDN interventions. The implementation of LDN is managed at the landscape level through integrated land use planning, while achievement is assessed at national level. Monitoring LDN status involves quantifying the balance between the area of gains (significant positive changes in LDN indicators) and area of losses (significant negative changes in LDN indicators), within each land type across the landscape. The LDN indicators (and associated metrics) are land cover (physical land cover class), land productivity (net primary productivity, NPP) and carbon stocks (soil organic carbon (SOC) stocks). The LDN conceptual framework comprises five modules: A: Vision of LDN describes the intended outcome of LDN; B: Frame of Reference clarifies the LDN baseline; C: Mechanism for Neutrality explains the counterbalancing mechanism; D: Achieving Neutrality presents the theory of change (logic model) articulating the impact pathway; and E: Monitoring Neutrality presents the LDN indicators. Principles that govern application of the framework provide flexibility while reducing risk of unintended outcomes.